Terrestrial orchids: The Hidden Jewels of Kamrup, Assam, India - Mustafizur , R; Rakesh , K; Deepjyoti , M (Plant Science Today, 2026)
The present study investigates the diversity of terrestrial orchid species in Kamrup district, Assam, based on extensive field surveys conducted across all the season from 2021 to 2025. The study employed with herbarium preparation and identification followed by standard protocol and using authentic literature. A total of 10 species were collected, representing 8 genera, with Zeuxine being the most dominating with 3 species. Each species described included their taxonomy, habitats and flowering periods. Most importantly, the work reports four rare species which underpin the ecological importance and conservation priority of these ground orchids in Kamrup. This work highlights the need to focus on understudied terrestrial orchids to protect and conserve them. Conserving orchids is essential because they are highly sensitive ecological indicator and contribute significantly to the ecosystem stability.